Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Determination of silicon. Ferrosilicon, ferrosilicomanganese and ferrosilicochromium: gravimetric method Part 3.26.5, (28th February 1985) - British Standards Institution,
No abstract available